Self-consistency in Bicultural Persons: Dialectical Self-beliefs Mediate the Relation between Identity Integration and Self-consistency - Zhang, Rui; Noels, Kimberly A.; Lalonde, Richard N.; Salas, S. J. (Frontiers in Psychology, 2017)
Prior research differentiates dialectical (e.g., East Asian) from non-dialectical cultures (e.g., North American and Latino) and attributes cultural differences in self-concept consistency to naïve dialecticism. In this research, we explored the effects of managing two cultural identities on consistency within the bicultural self-concept via the role of dialectical beliefs. Because the challenge of integrating more than one culture within the self is common to biculturals of various heritage backgrounds, the effects of bicultural identity integration should not depend on whether the heritage culture is dialectical or not. In four studies across diverse groups of bicultural Canadians, we showed that having an integrated bicultural identity was associated with being more consistent across roles (Studies 1–3) and making less ambiguous self-evaluations (Study 4). Furthermore, dialectical self-beliefs mediated the effect of bicultural identity integration on self-consistency (Studies 2–4). Finally, Latino biculturals reported being more consistent across roles than did East Asian biculturals (Study 2), revealing the ethnic heritage difference between the two groups. We conclude that both the content of heritage culture and the process of integrating cultural identities influence the extent of self-consistency among biculturals. Thus, consistency within the bicultural self-concept can be understood, in part, to be a unique psychological product of bicultural experience.